Covid-19 reveals and further increases inequalities in water and sanitation - Mehta, Lyla; Ringler, Claudia (Institute of Development Studies, 2020)
We now know that handwashing with soap for 20 seconds can fight the spread of coronavirus. For most of us accessing water is as simple as turning on the taps in our kitchens and toilets. But for one third of humanity, handwashing remains out of reach: 2.5 billion people lack access to safe drinking water; equally distressing, 4.5 billion people, or more than half of humanity, have no access to adequate sanitation facilities, which further increases the risk of a Covid-19 spread.